Intravenous lidocaine for inducing remission of cluster period - Santos, Paulo Sérgio Faro; Iachinski, Renato Endler; Sato, Henry Koiti; Nascimento, Maria Tereza Moraes Souza; Souza, Ricardo Krause Martinez de; Rizelio, Vanessa; Kowacs, Pedro André (Headache Medicine, 2012)
Cluster headache is a rare clinical condition, classified by the IHS as a trigeminal autonomic cephalalgia. Some known abortive treatments are inhaled oxygen, subcutaneous sumatriptan, intravenous dihydroergotamine and intranasal lidocaine. However, previous case reports suggest that intravenous lidocaine may play a role in the treatment of cluster headache attacks. We describe a patient with refractory cluster headache, whose condition remitted after the use of intravenous lidocaine. Therapy with lidocaine was conducted without harm, and the remission after a "single shot" suggested this approach to be safe and desirable to be tried in patients with cluster headache..